THE CORPORA-ORIENTED PROJECTS AND COURSES – INNOVATION OF THE UNIVERSITY LIFE - Tvaltvadze, Darejan; Gvelesiani, Irina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The advancement of computer technologies opened up a bunch of opportunities in different spheres of life. Computer science has revolutionized the modes of studying and researching. The educators and policy makers started modernization of educational programs in accordance to the latest achievements in the field. The present paper deals with the presentation of the progressive university courses as well as the projects (winter schools, Akaki Shanidze’s Digital Library and Text Corpus, etc.) facilitating the integration of corpora in teaching and researching. The major accept is put on the successful modes of the enhancement of the learners’ digital skills (operation, application, problem solving, critical thinking, etc.), corpus-building abilities (annotation, orientation towards the scientific metalanguage, enrichment of metadata, etc.), corpora-based analysis (proper coinage, finding equivalency, plying with concepts and terms, etc.) as well as the corpus-oriented research. Determination of the major challenges and outcomes of the projects and courses, discussion of some gaps, introduction of the convenient opportunities of their “filling” – these are the major issues of the paper. The methodology of research includes observation, analysis and evaluation of the ongoing processes.